More Than Fiscal The Intergenerational Report, Sustainability and Public Policy in Australia - Hall, Jane; Podger, Andrew; Woods, Mike (ANU Press, 2023)
Every five years, the Australian treasurer is required to publish an intergenerational report (IGR), which examines the long-term sustainability of current government policies and seeks to determine how demographic, technological and other structural trends might affect the economy and the budget in coming decades. Despite these lofty objectives, the five IGRs produced from 2002 have received only muted applause. Critics say that they are too mechanical, too narrow and too subject to the views of the government of the day and that they don't provide the intended wake-up call for public understanding of looming economic, social and environmental issues. This analysis of the most recent IGR (2021) is based on a workshop hosted by the Academy of the Social Sciences in Australia. While finding that the 2021 IGR is an improvement on the previous report (2015), the authors identify several fiscal and broader policy issues that deserve greater attention, including Australia's structural deficit, rising inequality and the impacts of climate change. They argue that the report fails to discuss the policies required to support greater resilience against future shocks, including the case for earlier budget repair. They propose that future IGRs be prepared with greater independence, cover all levels of government, have more transparent analysis and draw upon a wider 'wellbeing' approach to long-term sustainability. This book aims to attract close attention from public officials and politicians and generate constructive debate in the community.